OVERCOMING TERRORISM THREATS IN AIR FORCE BASE : CASE STUDY OF HALIM PERDANAKUSUMA AIR FORCE BASE - Sony Aji Pramono; Arfin Sudirman; Yusa Djuyandi (Aliansi, 2022)
ABSTRACT: Terrorism is one form of transnational crime and is very threatening tranquility and peace. In Indonesia, terrorism crimes often occur and consume victims that are not small in number from their own citizens or from foreign nationals. The purpose of the study "Overcoming Terrorism Threats at Air Base: Study of terrorism threat prevention cases at Halim Perdanakusuma Air Base" is to describe and analyze the handling of terrorism threats at the Base Air both in terms of policy and technical. The indicators used in this study are the ability of the Air Base and Halim Perdanakusuma Airport to be viewed from aspects of human resources, infrastructure, operations, supervision and equipment. The informants in this study were Air Base personnel, Angkasa Pura and officials in the Halim Perdanakusuma Air Base area. The research data is preceded by collecting secondary data and then followed by interviews and observation methods. Based on the results of the research carried out, it was obtained the results that counterterrorism at Halim Perdanakusuma Air Base was seen from the aspect of human resources, infrastructure, operations, supervision and equipment was still not optimal. So it needs a method that is solved in an innovative idea where it will indirectly provide input in improving terrorism threat control at Halim Perdanakusuma Air Base and Halim Perdanakusuma Airport.